Association of regional and cultural factors with the prevalence of rheumatoid arthritis in the mexican population (2015)
Background The overall estimated prevalence of rheumatoid arthritis (RA) in Mexico is 1.6%, but there are major variations in different geographic areas of the country. Objective This study aimed to determine the impact of individual and regional variables on the geographic distribution of RA in Mexico. Methods This multilevel analysis used data from a cross-sectional study that investigated the prevalence of RA among 19,213 individuals older than 18 years throughout 5 geographic regions in Mexico. Logistic regression models were used to determine predictors of RA, including individual and regional variables as well as cultural factors. Adjusted odds ratios (ORs) and 95% confidence intervals (CIs) were determined. Results The prevalence of RA varied from 0.77% to 2.8% across the 5 regions. Individual factors associated with RA were sex (OR, 2.32; 95% CI, 1.74–3.07), previous medical diagnosis of RA (OR, 3.32; 95% CI, 2.19–2.20), disability (OR, 2.07; 95% CI, 1.48–2.93), and the 56- to 65-year age group (OR, 1.95; 95% CI, 1.08–3.74). The regional factor of speaking an indigenous language had an OR of 2.27 (95% CI, 1.13–4.55). Conclusions Various individual and regional factors were associated with variations in the prevalence of RA in the Mexican population.